The unreasonableness of the imperative: Macario by Juan Rulfo (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
The article explains the functioning of the dominant discourse and its system of references in Macario (El llano en llamas, 1953) by Juan Rulfo (1917-1986). It proposes a reading of the story as an allegory of the domination of a dictatorship and the state of alienation suffered by the Mexican people during the period immediately preceding the Mexican Revolution (1910). To achieve this purpose, the socio-semiotic status of the speaking subject and the convergence network of the signs that define it are widely analyzed. Thus, it is possible to highlight a precise codification of social elaborations in the discursive structure, which permeates the perception displayed by the figure of the subject of the enunciation.
Keywords: Juan Rulfo; Macario; Mexican literature; alienation